Is the clinical performance of internal conical connection better than internal non-conical connection for implant-supported restorations? A systematic review with meta-analysis of randomized controlled trials - Rodrigues, Vitor Venâncio Moreira; Faé, Daniele Sorgatto; Rosa, Cleber Davi Del Rei Daltro [UNESP]; Bento, Victor Augusto Alves [UNESP]; Lacerda, Mariane Floriano Lopes Santos; Pellizzer, Eduardo Piza [UNESP]; Lemos, Cleidiel Aparecido Araujo (Wiley, 2023)
Purpose: To evaluate bone loss, prosthodontics and biological complications, and implant survival rates of internal conical connections (ICC) compared with internal non-conical connection (INCC) implants. Methods: The systematic review was registered on PROSPERO (CRD42021237170). Meta-analysis was performed using standardized mean difference (SMD) for bone loss and risk ratio (RR) for implant survival and complication rates. Risk of bias analysis was evaluated using RoB 2.0, whereas the GRADE tool was used to evaluate the certainty of evidence. A systematic search of the PubMed, Web of Science, Embase, Cochrane, and ProQuest databases was performed independently by two reviewers for articles published up to March 2022. The search criteria had no language or publication date restrictions. Handsearching analysis was performed in the reference list of potential articles. Results: Twelve randomized clinical trials, including 678 patients and 1006 implants (ICC [n = 476]; INCC [n = 530]), were included. Meta-analysis revealed that ICC demonstrated a lower risk for marginal bone loss (SMD: −0.80 mm; p = 0.004) and prosthodontics complications (RR: 0.16; p = 0.01) than INCC. However, both internal connections demonstrated no significant difference in implant survival rates (RR: 0.54; p = 0.10) and biological complications (RR: 0.90; p = 0.82). The overall risk of bias revealed some concerns and a low risk of bias for most of the included studies. However, the certainty of evidence of outcomes was considered low to moderate. Conclusion: ICC may be considered a more favorable treatment option than INCC owing to greater preservation of peri-implant bone tissue and a lower probability of prosthodontics complications. However, well-conducted studies with long-term follow-up are warranted.
Keywords: implant–abutment; internal butt joint; internal hexagon; tapered; tri-channel